Behaviour of brand switching of milk product for young children aged 1-3 years in consumers of middle to lower socioeconomic class in urban communities in malang. Issue 1 (November 2021) - Sunardi; Mulyo, J H; Irham; Jamhari
Abstract: A total of 56.7% of Indonesia's population today is concentrated in urban areas. More than 80% of Indonesians belong to the middle and lower socioeconomic class and this segment is the biggest consumer of milk products for young children aged 1-3 years called growing-up milk (GUM). Understanding the brand and customer behaviour is significantly important. This study aimed to examine the behavior of GUM brand switching on middle to lower socioeconomic class consumers in urban communities. The research was conducted in Malang Municipality, East Java Province, using guided interviews with questionnaires. The research respondents were 102 consumers of GUM that were selected by proportional random method in all five sub-districts. The data were processed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that the prior experience in purchasing variables had a highly significantly negative effect and the consumer dissatisfaction had a significantly positive effect on the process of brand switching for consumers of GUM products. Empty product stock in the store is one of the real examples of bad prior experience as well as dissatisfaction of the consumers that trigger them to change the old brand to new brand. The GUM companies have to maintain product suppliability.